1988
DOI: 10.1161/01.str.19.8.1008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of effects of kappa-opioid agonists on postischemic hippocampal CA1 neuronal necrosis in gerbils.

Abstract: The ability of the K-opioid receptor agonists U50488H and U62066E (spiradoline mesylate) compared with the non-K close structural analogue U54494A to affect postischemic necrosis of the selectively vulnerable hippocampal CA, neurons was examined in male Mongolian gerbils. The gerbils were treated with either saline vehicle or 10 mg/kg i. considerable interest has developed concerning the possible role of endogenous opioids in ischemic pathophysiology and neuronal degeneration. Based on the anti-ischemic action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…However, some investigators [39] did not find naloxone effective in cerebral ischaemia. Recent experimental studies have demonstrated the existence of at least three receptor subtypes for the endogenous opioid peptides and among them, kappa-opioid receptor binding was increased after ischaemic injury and activation of a kappa-opioid receptor system contributed to exacerbate cerebral ischaemia, while more recent studies [10,21,34] [14] have reported that the kappa agonist served to restore protection. Baskin and his colleagues [2] evaluated the therapeutic efficacy of variable kappa opioid agonists for delayed treatment of experimental focal cerebral ischaemia.…”
Section: Cerebral Ischaemia and Kappa Opioidsmentioning
confidence: 99%
“…However, some investigators [39] did not find naloxone effective in cerebral ischaemia. Recent experimental studies have demonstrated the existence of at least three receptor subtypes for the endogenous opioid peptides and among them, kappa-opioid receptor binding was increased after ischaemic injury and activation of a kappa-opioid receptor system contributed to exacerbate cerebral ischaemia, while more recent studies [10,21,34] [14] have reported that the kappa agonist served to restore protection. Baskin and his colleagues [2] evaluated the therapeutic efficacy of variable kappa opioid agonists for delayed treatment of experimental focal cerebral ischaemia.…”
Section: Cerebral Ischaemia and Kappa Opioidsmentioning
confidence: 99%
“…Several other substances, including kappa-agonists such as /-spiradoline and U622066 [87]. thyrotropin releasing hormone analogues [88] and insulin [89] protect against damage to CA 1 cells.…”
Section: Platelet-activating Factor (Paf) Antagonistsmentioning
confidence: 99%
“…Agents that selectively stimulate this system have been shown to reduce post-ischemic delayed neu ronal death in the gerbil [43]. Whether this effect is due to a reduction in acute neuronal swelling by osmotic effects or to a more direct receptor-mediated protection is not known.…”
Section: Inhibitory Neural Agonistsmentioning
confidence: 99%